Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Get quick and reliable answers to your questions from a dedicated community of professionals on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To model the transformation of a point [tex]\((x, y)\)[/tex] through a series of geometric operations—translation, reflection, and dilation—we can break down each step systematically.
1. Translation:
- Translate the point [tex]\((x, y)\)[/tex] 3 units to the right and 4 units down.
- The new coordinates [tex]\((x', y')\)[/tex] after translation are:
[tex]\[ x' = x + 3 \][/tex]
[tex]\[ y' = y - 4 \][/tex]
2. Reflection:
- Reflect the translated point across the x-axis.
- The coordinates [tex]\((x'', y'')\)[/tex] after reflection are:
[tex]\[ x'' = x' \][/tex]
[tex]\[ y'' = -y' \][/tex]
3. Dilation:
- Dilate the reflected point by a factor of 4 with the origin as the center of dilation.
- The coordinates [tex]\((x''', y''')\)[/tex] after dilation are:
[tex]\[ x''' = 4x'' \][/tex]
[tex]\[ y''' = 4y'' \][/tex]
Now, let's combine all these steps into one function [tex]\( f(x, y) \)[/tex]:
1. Translation:
[tex]\[ x' = x + 3 \][/tex]
[tex]\[ y' = y - 4 \][/tex]
2. Reflection:
[tex]\[ x'' = x' \][/tex]
[tex]\[ y'' = -y' \][/tex]
3. Dilation:
[tex]\[ x''' = 4x'' \][/tex]
[tex]\[ y''' = 4y'' \][/tex]
Substituting the intermediate steps into the final expressions:
1. Reflecting the translated coordinates:
[tex]\[ x'' = x' = x + 3 \][/tex]
[tex]\[ y'' = -y' = -(y - 4) = -y + 4 \][/tex]
2. Applying dilation:
[tex]\[ x''' = 4(x + 3) = 4x + 12 \][/tex]
[tex]\[ y''' = 4(-y + 4) = -4y + 16 \][/tex]
Thus, the function modeling the transformation [tex]\( f(x, y) \)[/tex] is:
[tex]\[ f(x, y) = (4x + 12, -4y + 16) \][/tex]
So, the final answer is:
[tex]\[ f(x, y) = (4x + 12, -4y + 16) \][/tex]
1. Translation:
- Translate the point [tex]\((x, y)\)[/tex] 3 units to the right and 4 units down.
- The new coordinates [tex]\((x', y')\)[/tex] after translation are:
[tex]\[ x' = x + 3 \][/tex]
[tex]\[ y' = y - 4 \][/tex]
2. Reflection:
- Reflect the translated point across the x-axis.
- The coordinates [tex]\((x'', y'')\)[/tex] after reflection are:
[tex]\[ x'' = x' \][/tex]
[tex]\[ y'' = -y' \][/tex]
3. Dilation:
- Dilate the reflected point by a factor of 4 with the origin as the center of dilation.
- The coordinates [tex]\((x''', y''')\)[/tex] after dilation are:
[tex]\[ x''' = 4x'' \][/tex]
[tex]\[ y''' = 4y'' \][/tex]
Now, let's combine all these steps into one function [tex]\( f(x, y) \)[/tex]:
1. Translation:
[tex]\[ x' = x + 3 \][/tex]
[tex]\[ y' = y - 4 \][/tex]
2. Reflection:
[tex]\[ x'' = x' \][/tex]
[tex]\[ y'' = -y' \][/tex]
3. Dilation:
[tex]\[ x''' = 4x'' \][/tex]
[tex]\[ y''' = 4y'' \][/tex]
Substituting the intermediate steps into the final expressions:
1. Reflecting the translated coordinates:
[tex]\[ x'' = x' = x + 3 \][/tex]
[tex]\[ y'' = -y' = -(y - 4) = -y + 4 \][/tex]
2. Applying dilation:
[tex]\[ x''' = 4(x + 3) = 4x + 12 \][/tex]
[tex]\[ y''' = 4(-y + 4) = -4y + 16 \][/tex]
Thus, the function modeling the transformation [tex]\( f(x, y) \)[/tex] is:
[tex]\[ f(x, y) = (4x + 12, -4y + 16) \][/tex]
So, the final answer is:
[tex]\[ f(x, y) = (4x + 12, -4y + 16) \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.